Mediterranean diet and life expectancy; beyond olive oil, fruits, and vegetables. Issue 6 (November 2016) - Martinez-Gonzalez, Miguel A.; Martin-Calvo, Nerea
Abstract : Purpose of review: The recent relevant evidence of the effects of the Mediterranean diet (MedDiet) and lifestyle on health (2015 and first months of 2016). Recent findings: Large observational prospective epidemiological studies with adequate control of confounding and two large randomized trials support the benefits of the Mediterranean dietary pattern to increase life expectancy, reduce the risk of major chronic disease, and improve quality of life and well-being. Recently, 19 new studies from large prospective studies showed – with nearly perfect consistency – strong benefits of the MedDiet to reduce the risk of myocardial infarction, stroke, total mortality, heart failure, and disability. Interestingly, two large and well conducted cohorts reported significant cardiovascular benefits after using repeated measurements of diet during a long follow-up period. In addition, Prevención con Dieta Mediterránea, the largest randomized trial with MedDiet, recently reported benefits of this dietary pattern to prevent cognitive decline and breast cancer. Summary: In the era of evidence-based medicine, the MedDiet represents the gold standard in preventive medicine, probably because of the harmonic combination of many elements with antioxidant and anti-inflammatory properties, which overwhelm any single nutrient or food item. The whole seems more important than the sum of its parts.